PROBABILISTIC MODEL FOR ASSESSING ACCIDENT RATES - Shevtsova, Anastasia; Novikov, Aleksandr; Evtyukov, Sergey; Marusin, Alexey (Journal of Applied Engineering Science, 2023)
When working with accident rates, a specialist has to spend quite a lot of time to establish the main places of accidents, certain conditions in which they occurred, which is extremely necessary when determining measures aimed at reducing road accidents. As a result of the research, the authors processed a large amount of data - accident rates for 2015-2021, as a result of which certain dependencies were established between the considered indicators in relative data, which made it possible to develop a probabilistic model for calculating the necessary data with the ability to determine the required conditions. Based on the results obtained, the authors developed an algorithm, according to which procedures were determined when working with accident rates and an assessment of efficiency based on the calculation of the error was carried out. The results obtained allowed us to conclude that the developed probabilistic model and algorithm are effective, in view of the minimum error.